Exposure to 1, 3-Butadiene in the U.S. Population: National Health and Nutrition Examination Survey 2011–2016. (19th May 2021) - Nieto, Alma; Zhang, Luyu; Bhandari, Deepak; Zhu, Wanzhe; Blount, Benjamin C.; De Jesús, Víctor R.
Abstract: 1, 3-Butadiene is a volatile organic compound with a gasoline-like odour that is primarily used as a monomer in the production of synthetic rubber. The International Agency for Research on Cancer has classified 1, 3-butadiene as a human carcinogen. We assessed 1, 3-butadiene exposure in the U.S. population by measuring its urinary metabolites N -acetyl-S-(3, 4-dihydroxybutyl)-L-cysteine (34HBMA), N -acetyl-S-(1-hydroxymethyl-2-propenyl)-L-cysteine (1HMPeMA), N -acetyl-S-(2-hydroxy-3-butenyl)-L-cysteine (2HBeMA), and N -acetyl-S-(4-hydroxy-2-buten-1-yl)-L-cysteine (4HBeMA). Urine samples from the 2011 to 2016 National Health and Nutrition Examination Survey were analysed for 1, 3-butadiene metabolites using ultrahigh-performance liquid chromatography/tandem mass spectrometry. 34HBMA and 4HBeMA were detected in >96% of the samples; 1HMPeMA and 2HBeMA were detected in 0.66% and 9.84% of the samples, respectively. We used sample-weighted linear regression models to examine the influence of smoking status (using a combination of self-reporting and serum-cotinine data), demographic variables, and diet on biomarker levels. The median 4HBeMA among exclusive smokers (31.5 µg/g creatinine) was higher than in non-users (4.11 µg/g creatinine). Similarly, the median 34HBMA among exclusive smokers (391 µg/g creatinine) was higher than in non-users (296 µg/g creatinine). Furthermore, smoking 1–10, 11–20, and >20 cigarettes per day (CPD) was associated with 475%, 849%, and 1143% higher 4HBeMA ( p < 0.0001), respectively. Additionally, smoking 1–10, 11–20, and >20 CPD was associated with 33%, 44%, and 102% higher 34HBMA ( p < 0.0001). These results provide significant baseline data for 1, 3-butadiene exposure in the U.S. population, and demonstrate that tobacco smoke is a major exposure source.